2017
DOI: 10.1002/adfm.201703801
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Shielding Hybrid Nanogenerator for Health Monitoring and Protection

Abstract: Nowadays, mankind faces increasingly energy crisis and electromagnetic radiation pollution. An energy harvester with function of protecting human health from electromagnetic radiation is a desirable solution to this problem. Here, a stretchable electromagnetic shielding hybrid nanogenerator (ES-HNG) is reported which can not only scavenge thermal and mechanical energy from living environment but also protect and monitor human health. The ES-HNG is capable of transforming mechanical and thermal energy to electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 199 publications
(98 citation statements)
references
References 39 publications
0
98
0
Order By: Relevance
“…Recently, a variety of electrically conductive fillers including metallic nanowires and nanoparticles,2,5–7 liquid‐metal (LM) droplets,8–10 carbon‐based materials (e.g., graphene, carbon fibers, and carbon nanotubes)1,11,12 and 2D transition‐metal carbides13–15 have been incorporated into polymer matrix to yield EMI shielding polymer composites. While these composites are easily processable, lightweight, and mechanically flexible, their EMI shielding effectiveness (SE) is inevitably plagued by the reduction in electrical conductivity with the applied stretch,6–8,12,15,16 a common phenomenon in the current stretchable conductors 17–19.…”
mentioning
confidence: 99%
“…Recently, a variety of electrically conductive fillers including metallic nanowires and nanoparticles,2,5–7 liquid‐metal (LM) droplets,8–10 carbon‐based materials (e.g., graphene, carbon fibers, and carbon nanotubes)1,11,12 and 2D transition‐metal carbides13–15 have been incorporated into polymer matrix to yield EMI shielding polymer composites. While these composites are easily processable, lightweight, and mechanically flexible, their EMI shielding effectiveness (SE) is inevitably plagued by the reduction in electrical conductivity with the applied stretch,6–8,12,15,16 a common phenomenon in the current stretchable conductors 17–19.…”
mentioning
confidence: 99%
“…Textile‐based TENGs possess merits such as good air permeability, flexibility and large‐scale production, therefore are desirable for wearable applications. Textile‐based TENGs have been applied to serve as self‐powered sensors for healthcare such as detection of respiration and sleep monitoring …”
Section: Textile Tengs As Self‐powered Health Monitorsmentioning
confidence: 99%
“…The other type is that the TENG uses two whole pieces of textile as the substrates or triboelectric layers. Zhang et al reported a textile TENG‐based hybrid nanogenerator (HNG) that is able to monitor human abdominal respiration, with the function of protecting human health from electromagnetic radiation, as is shown in Figure . The TENG consists of a layer of conductive antielectromagnetic radiation fabric sandwiched between two layers of rubber.…”
Section: Textile Tengs As Self‐powered Health Monitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it cannot be directly used to drive most electronic devices which require a stable and continuous input power . The normal process is to transform the AC to direct current (DC) with a rectifier and then store the energy in an energy‐storage unit . Supercapacitor (SC) is an ideal candidate for green energy storage with high power density, excellent pulse charge–discharge character, superhigh cycling life, and safe operation .…”
Section: Introductionmentioning
confidence: 99%